FERGANA VALLEY AS SAGDIANA CITY ON THE SILK ROAD: A HISTORICAL AND CULTURAL REAPPRAISAL (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The Fergana Valley, located in the heart of Central Asia, has long been considered a fertile and strategic area of trade, agriculture, and cultural exchange. Historically, it was one of the important cities associated with Sogdiana, the ancient Iraniancivilization that flourished along the Silk Road.